PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP LITERASI DIGITAL DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA - Rizka Al - Hikmah; Ririn Andriani Kumala Dewi; Kiki Fatkhiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the lack of time efficiency during teaching and learning activities in math lessons, and when teachers integrate learning with technology, students are rarely involved in the use of ICT (Information and Communication Technology). The purpose of this study was to determine the effect of the Flipped Classroom learning model on digital literacy and student learning outcomes. In this study, the approach used was a quantitative approach with experimental methods and the research design used was True experimental in the form of Pretest - Posttest Control Group Design. The population of this study was all fifth-grade students of Riyadlul Muta'allimin Elementary School in the 2024/2025 academic year. By using a random sampling technique. Referring to the results obtained from data analysis, it obtained the calculation of the t-test (independent sample t-test) on digital literacy, namely (8.792)> (2.0423) and Sig (2-tailed) of 0.00 < α (0.05) and on the learning outcomes obtained the results of the mann whitney test with a value of z = -5.322 and Sig (2-tailed) of 0.00 < α (0.05). Based on the results of the data analysis, it show that there is an effect of the Flipped Classroom learning model on digital literacy and learning outcomes of fifth-grade students of Riyadlul Muta'allimin Elementary School in the 2024/2025 school year.